Tyrosine Kinase Inhibitor Post-Allogeneic Stem Cell Transplantation in Adult Philadelphia-Positive B-Acute Lymphoblastic Leukemia: State of the Art and Future Directions - Martina Canichella; Paolo de Fabritiis (Current Issues in Molecular Biology)
In a scenario characterized by continuous improvement in outcomes, Philadelphia chromosome-positive (Ph+) ALL, once considered a biologically defined subtype with one of the poorest prognoses, now includes patients achieving long-term survival even without allogeneic stem cell transplantation. First-line therapy is increasingly adopting a chemo-free approach, combining tyrosine kinase inhibitors (TKIs) with immunotherapy—specifically blinatumomab—which has resulted in high rates of complete molecular responses and improved survival outcomes. Within this paradigm shift, the allocation to transplantation is becoming increasingly selective and genomically oriented, focusing on patients with particularly unfavorable prognostic and predictive factors. For patients undergoing transplantation, maintenance therapy with TKIs has emerged as one of the most important strategies to reduce the risk of relapse. However, there remains considerable uncertainty regarding which patients benefit most from this approach, the optimal TKI agents, dosing strategies, and the duration of maintenance therapy. In this review, we aim to consolidate the available evidence on this topic, analyzing it in the context of the most recent clinical experiences.